Towards Sustainable Self-Compacting Concrete: Effect of Recycled Slag Coarse Aggregate on the Fresh Properties of SCC - Hisham Qasrawi (Advances in Civil Engineering)
Steel industry results in accumulation of steel slag wastes causing severe environmental problems. These wastes can be recycled and replace natural aggregates resulting in sustainable green concrete. In this research, natural aggregates in self-compacting concrete (SCC) are replaced, wholly or partly, by steel slag coarse aggregates that were produced by crushing by-product boulders obtained from the steel industry. Fresh properties, (workability, stability, bleeding, air content, and fresh density) are the crucial ones that affect the final properties of SCC. Therefore, it becomes important to evaluate the impact of SSA on the fresh properties of SCC mixes. The properties that are studied include stability, flowability, blocking, segregation, and bleeding. Furthermore, air content and fresh density are measured. In order to evaluate the impact of SSA on SCC properties, several testing methods are employed. Slump flow, V-funnel, column segregation, sieve segregation, segregation probe, U-shaped box, and VSI tests have been used in the study. The results show that it is possible to produce SCC using steel slag aggregate. Hence, green sustainable SCC can be produced. The results show that the fresh properties become sensitive for SSA replacement ratios exceeding 50%.